Raintree County - Ross Lockridge 1914-1948; Edmund Fuller (New York Dell Publishing Co, 1958)
A panoramic epic of the 19th century in Raintree County, Indiana, particularly of the Civil War and its effects.... which had no boundaries in time and space, where lurked musical and strange names and mythical and lost peoples, and which was itself only a name musical and strange
Keywords: Literature (3GdCOHs; General